Determinants of Client-Professional Relationship Quality in the Financial Planning Setting - Katherine Hunt; Mark Brimble; Brett Freudenberg (Australasian Accounting, Business and Finance Journal, 2011)
Advice provided by financial planners has the potential to impact the financial and emotional well being of clients. Despite the outcomes of quality financial planning relationships, there is little direct evidence to support the importance of ‘relationship quality’ in financial planning. Previous research has emphasised the importance of relationship quality in psychology, nursing, and business settings. This research investigates determinants of client-professional relationship quality in financial planning, measured in a survey of clients and financial planners regarding relationship factors of trust, engagement, empowerment, ownership, client activity and commitment. Ratings for relationship dimensions were compared between clients and financial planners, with financial planners found to overestimate their clients’ levels of trust and commitment and underestimate their client’s levels of empowerment. The relationship dimension of ‘trust’ was found to be critical for client-professional relationship quality.
Keywords: Financial Planning; Relationships; Ethics; Trust; Business Relationships; Relationship Quality